Personal reflections on basics of research workshop conducted by Journal of Pakistan Medical Association (JPMA) - Rida e Fatima; Syeda Zainab Ali (Journal of the Pakistan Medical Association, 2024)
Recognizing the importance of research in a medicalstudent's life, we were thrilled to volunteer as organizersfor JPMA's research workshop for undergraduate medicalstudents. This five-week long program, held on consecutiveSaturdays, commencing from 18th May 2024, aimed toequip participants with the fundamentals of research. Tomaintain the quality of the workshop, the participant poolwas kept limited to fourteen only. The workshop was heldat the premises of PMA. Every session consisted of twoclasses, each an hour long with a brief lunch break inbetween. Besides broadening our understanding onresearch basics, we hoped to gain valuable leadership andcommunication skills through this organizing experience. Continued...